- #36

StudentTM

- 21

- 0

Somebody suggested to me that

a_x = ( 30 (centripetal acceleration) * v * v_x1 ) / 60*60

a_y = (( 30 (centripetal acceleration) * v * v_y1 ) / 60*60 ) - 9,8

would be correct.

And

a_x = -39.8 * V_t * Vy_1 / (60 * 60);

a_y = 39.8 * V_t * Vx_1 / (60 * 60) - 9.8;

is wrong.

Why should it be like that?

Sorry guys, for dummy question, I really respect your patience with me, but .. How can I learn to understand these final equation? Where to start? Where do they come from exactly?

Voko your explanation for upper difficult equations makes sense for a start.

Where do I begin to study those final simplified equations?

For example - POSITION:

I see why there is '' x_2 = x_1 + (Vx_1) * delta_t ''

V * t = x

But how do I know V_x is constant?

VELOCITY:

Vx_2 = Vx_1 + Ax * delta_t

a * t = V ... I agree, but this time we are using equation for accelerated motion. Why? If we used an equation for constant velocity for position?

ACCELERATION:

Ax = -39.8 * V_t * Vy_1 / (60 * 60) or a_x = ( 30 (centripetal acceleration) * v * v_x1 ) / 60*60

This one I don't understand at all.

a_x = ( 30 (centripetal acceleration) * v * v_x1 ) / 60*60

a_y = (( 30 (centripetal acceleration) * v * v_y1 ) / 60*60 ) - 9,8

would be correct.

And

a_x = -39.8 * V_t * Vy_1 / (60 * 60);

a_y = 39.8 * V_t * Vx_1 / (60 * 60) - 9.8;

is wrong.

Why should it be like that?

Sorry guys, for dummy question, I really respect your patience with me, but .. How can I learn to understand these final equation? Where to start? Where do they come from exactly?

Voko your explanation for upper difficult equations makes sense for a start.

Where do I begin to study those final simplified equations?

For example - POSITION:

I see why there is '' x_2 = x_1 + (Vx_1) * delta_t ''

V * t = x

But how do I know V_x is constant?

VELOCITY:

Vx_2 = Vx_1 + Ax * delta_t

a * t = V ... I agree, but this time we are using equation for accelerated motion. Why? If we used an equation for constant velocity for position?

ACCELERATION:

Ax = -39.8 * V_t * Vy_1 / (60 * 60) or a_x = ( 30 (centripetal acceleration) * v * v_x1 ) / 60*60

This one I don't understand at all.

Last edited: